Description of Communal Domestic Wastewater Treatment Plant in Kelurahan Simokerto, Kecamatan Simokerto, Kota Surabaya - Oktina Purwatiningrum (JURNAL KESEHATAN LINGKUNGAN, 2018)
Domestic wastewater treatment is one of the environmental problems in Surabaya. Besides causing water pollution, wastewater also causeing health problems. A method to treat wastewater is Communal Waste Water Treatment Plant (WWTP). The effluent of WWTP is then reused by residents. The study aimed to describe the WWTP in Kelurahan Simokerto, Kecamatan Simokerto, Kota Surabaya, and compare wastewater parameters to the regulation. The study is a descriptive observational and cross-sectional research. The method used is interview with WWTP organizer and laboratory examination on 5 samples of influent and effluent parameters include pH, BOD, COD, TSS, oil and grease. All of influent and effluent parameters have already met domestic wastewater quality standards in Peraturan Gubernur Jawa Timur No. 72 Tahun 2013 so the effluent is safe to be discharged into the environment. Since the influent and effluent is below the maximum level of quality standards, the Communal WWTP in Kelurahan Simokerto hasn't already met standard for an appropriate WWTP. The experts need to do study about wastewater characteristics before building a WWTP so that the appropriate WWTP is obtainable. Moreover, they need to do in-depth study about factors that affect wastewater quality. It's necessary to arrange detailed SOP for routine operations and maintenance of WWTP accompanied by improvement of understanding of the organizer and citizens about the importance of communal WWTP as well as how to operate and maintain.